The morphological and anatomical properties of Melissa officinalis L. (Lamiaceae) - سلطان, عبير (Latakia University Journal -Biological Sciences Series, 2023)
This research investigated an accurate and detailed study of the morphological characteristics of all organs of Melissa officinalis L. , because of its medical importance and its natural distribution in our coastal area. Morphological study shows a hairy root system with numerous lateral roots, and an erect quadrangular stem. There are opposite decussate pairs of ovateto cordate green leaves. The anatomical study of the leaf showed that there is palisade tissue under the upper epidermis only in disk area. The anatomical study of stem showed that the stem is tetrangular in transversal sections and collenchyma tissues at angels . The results showed two types of trichomes glandular and e-glandular (non-glandular) hairs. Stomata are of Anomocytic type.